Caffeine Bitterness is Related to Daily Caffeine Intake and Bitter Receptor mRNA Abundance in Human Taste Tissue. (March 2017) - Lipchock, Sarah V.; Spielman, Andrew I.; Mennella, Julie A.; Mansfield, Corrine J.; Hwang, Liang-Dar; Douglas, Jennifer E.; Reed, Danielle R.
We investigated whether the abundance of bitter receptor mRNA expression from human taste papillae is related to an individual's perceptual ratings of bitter intensity and habitual intake of bitter drinks. Ratings of the bitterness of caffeine and quinine and three other bitter stimuli (urea, propylthiouracil, and denatonium benzoate) were compared with relative taste papilla mRNA abundance of bitter receptors that respond to the corresponding bitter stimuli in cell-based assays ( TAS2R4, TAS2R10, TAS2R38, TAS2R43, and TAS2R46 ). We calculated caffeine and quinine intake from a food frequency questionnaire. The bitterness of caffeine was related to the abundance of the combined mRNA expression of these known receptors, r  = 0.47, p  = .05, and self-reported daily caffeine intake, t (18) = 2.78, p  = .012. The results of linear modeling indicated that 47% of the variance among subjects in the rating of caffeine bitterness was accounted for by these two factors (habitual caffeine intake and taste receptor mRNA abundance). We observed no such relationships for quinine but consumption of its primary dietary form (tonic water) was uncommon. Overall, diet and TAS2R gene expression in taste papillae are related to individual differences in caffeine perception.